The divine face in four writers : Shakespeare, Dostoyevsky, Hesse, and C. S. Lewis - Hunt, Maurice, 1942- (Bloomsbury Academic, 2016)
An important contribution to studies in literature and religion, The Divine Face in Four Writers traces the influence of Christian and Classical prototypes in ideas and depictions of the divine face, and the centrality of facial expressions in characterization, in the works of William Shakespeare, Fyodor Dostoyevsky, Herman Hesse and C.S. Lewis. Maurice Hunt explores both the human yearning to see the divine face from post-Apostolic time to the 20th century, as reflected in religion, myth and literature by writers such as Augustine, Shakespeare, Hardy and Dostoyevsky, as well as the significance of the hidden divine face in writings by Spenser, Milton, Hesse and Lewis. A final coda briefly detailing Emmanuel Levinas's system of ethics, based on the human face and its encounters with other faces, allows Hunt to focus on specific moments in the writings of the four major writers discussed that have particular ethical value.